Effect of vitamin E supplementation on lipid profile in chronic renal patients on maintenance hemodialysis - (:unkn) unknown (My University, 1990)
There is a discrepancy in the literature concerning the effect of vitamin E administration on plasma lipids of healthy individuals and chronic renal patients on maintenance hemodialysis. In the present study, we have conducted a placebo-controlled, double-blind, randomized trial in which the effect of vitamin E supplementation on lipid profile of chronic renal patients on maintenance hemodialysis was examined. Vitamin E (600 IU/day) was administered for 8 weeks to 42 healthy individuals and 57 chronic renal failure patients on maintenance hemodialysis. The placebo group of healthy volunteers had significantly lower vitamin E levels when compared to the placebo group of chronic renal patients. There was a moderate increase in total cholesterol and a very significant increase in the HDL-cholesterol of chronic renal patients compared to their placebo controls. Our results showed that 8 weeks of vitamin E (600 IU/day) administration to chronic renal patients on maintenance hemodialysis definitely increased their HDL-C and to some extent their total cholesterol. Since patients with end-stage renal disease suffer from an increased mortality rate from atherosclerosis, vitamin E administration may very well be beneficial for these patients by increasing their HDL-C levels.